PELAKSANAAN KEGIATAN KELOMPOK KERJA KEPALA TK (K3TK) DI KECAMATAN SEDATI SEBAGAI UPAYA MENINGKATKAN KEMAMPUAN KEPALA TAMAN KANAK-KANAK DALAM PENGELOLAAN ADMINISTRASI SEKOLAH SEMESTER 2 TAHUN PELAJARAN 2017/2018 - Hamidah, Siti (incrementapedia, 2020)
The problem in this study is the low ability of the Kindergarten Head in managing school administration. This was proven by the incomplete management documents of the school administration by 30 Kindergarten Heads in Sedati District. The purpose of the study was to improve the ability of the Kindergarten Head in the Sedati District in the management of school administration. The research subjects were 30 Kindergarten Heads in Sedati District. This research was conducted in two cycles. The data collection method uses observation and documentation techniques. Data validation used in this action research is democratic, process and dialogic validation. Data analysis was performed by comparing results on initial conditions, results of cycle I, results of cycle II. The results showed that in the initial conditions 30 Kindergarten Heads were declared unable to manage administration well or 0% with an average rating of 40.29, increasing to 12 Kindergarten Heads or 40% in the first cycle with an average yield of 58.75 and 100% in the second cycle with the acquisition of an average value of 77.89. The explanation of the criteria for the value of the initial conditions is less, increasing to enough and good in the last cycle. looking at the data obtained from the results of research in this school ction research activity, it can be concluded that the K3TK activities in the Patronage of Sedati Subdistrict conducted by school supervisors for 30 Kindergarten Heads were declared successful in increasing the ability of the Kindergarten Head in managing school administration.